Feminist Activism as Interfaith Dialogue: A Lesson from Gangjeong Village of Jeju Island, Korea - Pae, Keun-Joo Christine (Journal of Korean religions, 2014)
How do the religious engage with one another in Gangjeong village, Jeju when faced with the perceived threat to peace and human security presented by the construction of a naval base in the village? How do their religious teachings and spiritual practices motivate them to actively participate in peace activism? Exploring women’s roles in peace activism at Gangjeong, this essay suggests the dialogue of peacemaking activism informed by feminist activism as a desirable model for interfaith dialogue in Korea. Feminist activism is understood as a way of constructing shared power relations in every part of human society. Considering Korea’s particular geopolitics (i.e. ideological division and excessive militarization of Asia Pacific), this essay argues that first, the Korean religious should pay attention to the role of patriarchal masculinity in militarism and interfaith dialogue; second that a Korean model of dialogue in peace activism should incorporate gender perspectives by seriously considering women’s day-to-day activities as forms of spiritual practice; and third, that those who participate in the dialogue of peace activism should seek out practical ways of creating shared power relations among all living beings and liberate themselves from the fear fed by militarism.